Improvement of the Engineering Properties of A-3 Soil by the addition of plastic particles - Zaynab Alqadhqad; Shrifa Elhamroni; Abdalla Aboulkasim (AlQalam Journal of Medical and Applied Sciences, 2025)
This paper aims to investigate the use of plastic waste in sand A3. The particles of plastic materials utilized for this purpose were sourced from natural waste in the Garabulli region. Four different proportions of plastic strips (0%, 5%, 10%, and 15%) were mixed with the original dry soil. The mechanical and physical properties of the soil were then analyzed and compared before and after the addition of plastic waste. The results indicated an improvement in the soil’s shear strength, along with an increase in maximum dry density and a reduction in the soil void ratio.